Urgensi Kekuatan Harapan terhadap Self Concept - Kaisa Azizah Azzahra (Gunung Djati Conference Series, 2023)
Humans as creatures that live with dreams and ambitions, make the goals of their lives inserted into their hopes. Through this hope, humans can get encouragement to take actions that encourage someone to try to be able to obtain the goals to be achieved. The attractiveness of a motivation makes a person have a sense of fighting power to realize his hopes. The process of learning to internalize the environment becomes a pathway in the formation of one's personality through habits in building self-concept. This study uses a qualitative descriptive-analytical approach through secondary data sources in the form of books, journal articles, and others. The results of this study discuss the correlation between the strength of a person's expectations and his self-concept by making motivation a motivating factor for a person to realize his hopes.